2020
DOI: 10.3201/eid2611.203504
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Candida auris Infections in Critically Ill Coronavirus Disease Patients, India, April–July 2020

Abstract: In New Delhi, India, candidemia affected 15 critically ill coronavirus disease patients admitted to an intensive care unit during April–July 2020. Candida auris accounted for two thirds of cases; case-fatality rate was high (60%). Hospital-acquired C. auris infections in coronavirus disease patients may lead to adverse outcomes and additional strain on healthcare resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
297
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(328 citation statements)
references
References 14 publications
6
297
1
4
Order By: Relevance
“…Moreover, we postulated a negative impact of COVID-19 on antimicrobial stewardship programs, an issue reported in a speculative manner in various reviews and editorials. To the best of our knowledge, only one real-life report describes the acquisition of CR-Kp colonization among COVID-19 patients [15], while two centers reported an increase in C. auris infections in COVID-19 patients [16,17]. We supposed that the main drivers of an increase in antimicrobial resistance during COVID-19 in our hospital were the use of broad-spectrum antimicrobials and horizontal spread of resistant strains.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, we postulated a negative impact of COVID-19 on antimicrobial stewardship programs, an issue reported in a speculative manner in various reviews and editorials. To the best of our knowledge, only one real-life report describes the acquisition of CR-Kp colonization among COVID-19 patients [15], while two centers reported an increase in C. auris infections in COVID-19 patients [16,17]. We supposed that the main drivers of an increase in antimicrobial resistance during COVID-19 in our hospital were the use of broad-spectrum antimicrobials and horizontal spread of resistant strains.…”
Section: Discussionmentioning
confidence: 87%
“…Chowdhary et al. [ 6 ] theorized that transmission of COVID-19-associated C. auris by health personnel is unlikely because of the use of PPE. The 15 isolates of C. auris were non-susceptible to AMB and FLU, which are the main antifungal drugs used in most of the hospitals in Mexico.…”
mentioning
confidence: 99%
“…Several studies-from, in particular, Germany, Italy and the US-have reported outbreaks or an increase in infections with and/or acquisition of multidrug-resistant bacteria during the COVID-19 pandemic [9][10][11][12]. Further studies have reported cases of antimicrobial-resistant invasive fungal infections in COVID-19 patients [13,14], and one case of azole-resistant Aspergillus spp. infection in an immunocompetent COVID-19 patient [15].…”
mentioning
confidence: 99%